Implementation of Integrative-Based Islamic Educational Psychology Module Development: (Cognitive and Transcendental Studies) - Jannah, Raudhatul; Muhammad, Muhammad; Haniif, Ibnu; Lubis, Lahmuddin (Pusdikra Publishing, 2025)
This study aims to analyze the implementation of the development of an integrative-based Islamic educational psychology module based on cognitive and transcendental studies. This research employed a qualitative method with a literature review approach, collecting data from various sources such as books, articles, journals, and so on. The results of this study indicate that the development of an integrative-based Islamic Educational Psychology module, which combines cognitive and transcendental studies, has proven effective in improving the quality of holistic and meaningful learning. This module is designed not only to strengthen students' understanding of cognitive concepts in educational psychology but also to instill the spiritual and transcendental values that characterize Islamic education. The integrative approach used in this module bridges scientific aspects and faith values, enabling students to develop not only intellectually but also morally and spiritually. The use of this module has also shown an increase in active student engagement, in-depth understanding of the material, and positive attitudes toward Islamic values in the learning process. Therefore, this module is highly relevant for implementation in Islamic educational environments to shape the character of students who are well-rounded, knowledgeable, and possess noble character.